(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
"Legal Overview of the Effectiveness of the Lease Agreement to Rent a House in Makassar City". Under the guidance of Muhammad Rustan as Chief Advisor and Sahban as Advisor. This study aims to determine the effectiveness of the rental agreement for renting a house in Makassar City in making agreements between home owners and tenants so as to provide legal certainty for both parties. This research uses empirical research. The location of this research was carried out on Sultan Alauddin Street, Bosowa Housing Complex, Makassar City and West Kabila Street. Types and sources of data used are primary data and secondary data. Data collection techniques, library research and field research. Data analysis, namely data that has been obtained both primary and secondary data will then be processed and analyzed to produce conclusions, then presented descriptively.